The Role of Artificial Intelligence in Enhancing Creative and Financial Performance in the Creative Sector - Prasetyanto, Didik; Suhardjanto, Djoko; Probohudono, Agung Nur; Widarjo, Wahyu (Journal of Ecohumanism, 2024)
This research aims to investigate how Artificial Intelligence (AI) integration enhances creative productivity and leads to improved outcomes in financial performance. The advancement of technology enables the improvement of knowledge sharing, absorptive capacity, skills, and innovation, fostering greater efficiency in achieving organizational goals. This pioneering research develops a holistic framework that integrates AI as a moderating factor, highlighting its transformative role in achieving a competitive advantage. A sample of 499 MSMEs in the Indonesian creative sector was obtained from a total of 34,000 HIPMI members through purposive and judgment sampling methods. Using the scrutinize method, this study provides an in-depth analysis of the interactions between technological advancements and organizational capabilities, offering strategic insights for sustainable growth. Regression analysis results indicate that knowledge sharing, absorptive capacity, skills, and innovation have a significant and positive effect on the creative performance. AI also has a significant positive impact on financial performance. The integration of AI strengthens the association between innovation and creative performance, but it does not reveal a substantial impact on the link of knowledge sharing, absorptive capacity, and skills with creative performance. This study provides theoretical and practical contributions to support decision-making in technology policy in the creative sector.